Safety and efficacy of elbasvir and grazoprevir for treatment of hepatitis C. Issue 6 (2nd June 2016) - Carrion, Andres F.; Martin, Paul
ABSTRACT: Introduction: The combination of elbasvir and grazoprevir in a single co-formulated tablet is highly effective for treatment of hepatitis C virus (HCV) infection. This regimen affords profound inhibition of NS3/4A protease and NS5A activity, resulting in potent activity against HCV genotypes 1, 4, and 6 with high rates of sustained virological response. Areas covered: This review covers the mechanism of action, pharmacokinetics, clinical applications, efficacy and safety profile of elbasvir/grazoprevir including special populations such as individuals with compensated and decompensated cirrhosis, HCV/HIV co-infection, advanced chronic kidney disease, and those that previously failed antiviral therapy. Expert opinion: Elbasvir/grazoprevir is an effective antiviral regimen for treatment of genotypes 1 and 4 and has a very favorable safety profile based on extensive data from several pre-licensure clinical trials that included patient subgroups at increased risk of toxicity. This regimen is currently the only one licensed for use in individuals with advanced chronic kidney disease requiring hemodialysis.